Hypothalamic-Pituitary-Adrenal Suppression and Iatrogenic Cushing's Syndrome as a Complication of Epidural Steroid Injections. (7th August 2013) - Leary, Joyce; Swislocki, Arthur
Abstract : Epidural steroid injections are well accepted as a treatment for radicular back pain in appropriate candidates. While overall incidence of systemic side effects has not been well established, at least five biochemically proven cases of iatrogenic Cushing's Syndrome have been reported as complications of epidural steroid treatment. We present an additional case of iatrogenic Cushing's Syndrome and adrenal suppression in a middle-aged woman who received three epidural steroid injections over a four-month period. We review this case in the context of previous cases and discuss diagnostic and management issues.